Effects of Dietary Male and Female Ferula Eleaochytris Powder on Growth Performance and Body Components of Broiler Chicks - Metin Duru; Ahmet Şahin (Turkish Journal of Agriculture: Food Science and Technology, 2015)
The purpose of this study was to investigate the effects of dietary addition of male and female Ferula eleaochytris powder (FEP) on growth performance and body components of broilers (Ross-308). Treatment groups were allocated to 5 dietary in which 0 (control), 5 g and 10 g male FEP, 5 g and 10 g female FEP doses per kg commercial broiler diet. In total, 80 male broiler chicks (1-d old) in which 16 animals in each group were used in study. Body weight gain and feed intake were monitored weekly for 6 weeks. Forty two days old broiler chicks were slaughtered to determine the possible changes in body components. The results of the study indicated that FEP had no effect on any parameters. However; the weight of the control group gave higher values than 5 g male Ferula group. In conclusion the measured parameters had no effect between all groups.